Effort Of Achieving Dream Reflected In Laura Fitzgerald's Veil Of Roses (2006): An Individual Psychological Approach - Hapsari, Rizki Ayu; , Drs. Abdillah Nugroho, M.Hum; , Nur Hidayat, S.Pd (2013)
This research investigated how is effort of Tamila Soroush influence her personality in Laura Fitzgerald‟s Veil of Roses novel, especially viewed from individual psychological approach. The objectives of the research are to analyze the novel based on the structural elements of the novel and to analyze the personality structure of major character based on the individual psychological approach. The research paper belongs to the qualitative research. The object of the study is the effort of Tamila Soroush in Veil of Roses. The data source comes from primary data source that is the Veil of Roses novel and the secondary data sources are other sources related to the movie. The method of data analysis used in this study is descriptive analysis. From the result of analysis, it can be drawn some conclusions. Firstly, the structural elements of the novel present a good unity because it has related one to another. Laura Fitzgerald extends the theme of this novel is about the struggling of woman to reach her dreams. Secondly, based on individual psychological approach analysis this novel reflects Tamila effort to stay in America.